Alice ainda mora aqui: narrativa juvenil contemporânea - Alice Áurea Penteado Martha (Estudos de Literatura Brasileira Contemporânea)
The understanding that lies in the possibility of recognizing in the texts we read what we experience in real life, express, translate and nourish our emotions and feelings of pain or happiness, making us approach the identity of the “subject- matter” leading us towards choices, relationships and extreme situations. It typifies on the fiction plan, evolution stages experienced by humans, and which may translate, at the same time, ways of preserving the cultural identity and participate in the process of universalization. Such aspects shall be emphasized in juvenile narratives selected from the contemporary Brazilian literature, such as Laura Bergallo’s “Alice no espelho” [Alice in the Mirror] and Jorge Miguel Marinho’s “A maldição do olhar” [The Curse of the Gaze]. This, if we mainly consider the diversity of views offered by the internal perspective of the texts, the interaction of which allows the aesthetic object to emerge, according to Wolfgang Iser.